MENGUJI PENGARUH KEPEMIMPINAN TERHADAP PERILAKU KERJA DAN KINERJA KARYAWAN (Studi Pada Kantor Imigrasi Kelas I Khusus Ngurah Rai) - Saktinegara, Jerry Risnandar; Wardana, I Made; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Leaders of the organization must learn and understand the behavior of subordinates and pushed to the achievement of organizational goals effectively. This study aimed to analyze the influence of leadership on work behavior and performance of employees and to analyze the effect of the work on the performance of the employee's behavior. This study uses 92 respondents employees in Kantor Imigrasi Kelas I Khusus Ngurah RaiBali. Data was collected by distributing questionnaires to the respondents. The collected data were analyzed by using Partial Least Square. The research showed that leadership is a significant positive effect on work behavior, work behavior is positive influence on employee performance. The study also showed  that leadership is not significant positive effect on employee performance. The implications of this study emphasize the important role of leadership in improving employee behavior. The performance of employees will be increased if the leadership has integrity and is able to carry out the vision and  mission organization so employees are more passionate in carrying out the work.
Keywords: leadership, employee behavior, employee performance.